PERMAINAN TRADISIONAL LOMPAT TALI MERDEKA SEBAGAI MEDIA PELAKSANAAN PROSES GAME STAGE DI SD NEGERI 94 PEKANBARU - Tria Paradisa; Hesti Asriwandari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The traditional game lompat tali merdeka is a name of traditional game for those who livein Riau Province. The naming of this game has something to do with the movement of playersespecially in the last leap; the rope is stretched by a high-fisted player held up in the air. The fistis almost similar to what the fighters do when they say the word